Lokalklimaanalyse for bygg og utemiljø - Størkersen, Ellen Gjersdal (UiT Norges arktiske universitet, 2016)
Rapporten tar for seg en lokalklimatisk analyse i forbindelse med utbygging av felt B10 og B11 på Skytterhusfjellet, Kirkenes. Det teoretiske grunnlaget tar for seg klimatiske faktorer, komfort og strømningslære. Numeriske simuleringer er utført for å studere virkninger av snø- og vindforhold. Based on theoretical aspects on the influence from climatic factors, comfort and fluid mechanics, this report provides a local climatic analysis focusing on the development of project area B10 and B11 at Skytterhusfjellet in Kirkenes. Numerical simulations concerning wind and snowdrift are performed to examine the impact of different design ideas. Abstract: Based on theoretical aspects on the influence from climatic factors, comfort and fluid mechanics, this report provides a local climatic analysis focusing on the development of project area B10 and B11 at Skytterhusfjellet in Kirkenes. Numerical simulations concerning wind and snowdrift are performed to examine the impact of different design ideas.